THE DEFINITION OF ECONOMIC EFFICIENCY OF THE PASSENGER CAR OF A NEW TYPE - Gnennyi, M. V.; Gnennyi, O. M. (Science and Transport Progress, 2007)
A technical approach to cost efficiency determination of new type of passenger cars introduction is proposed, based on modern methods of defining the efficiency of innovations. This includes a proposed technique for assessing the uncertainties and risks with the use of method of statistical testing. A model has been developed for determining efficiency of introduction of the passenger transformer car produced by public corporation Dneprovagonrembud.